3-Year Follow-Up of Nonextraction Crowded Cases Treated With the Damon System - Faruk Ayhan Başçiftçi; Zeliha Müge Baka; Sinem Bayram; Emire Aybüke Erdur (Galenos Yayinevi, 2014)
Objective:The aim of this retrospective study was to investigate treatment efficiency and 3-year follow-up stability of the Damon system by evaluating peer assessment rating (PAR) index, posteroanterior-lateral cephalometric changes, and the intercanine and intermolar widths.Materials and Methods:Fifty-five patients treated with a 0.022-inch slot Damon D3 MX bracket system were evaluated in this study. Cephalometric radiographs, dental models, and PAR scores were measured and evaluated pretreatment (T1), posttreatment (T2), and 3 years after treatment (T3). Repeated-measures analysis of variance (ANOVA)/paired t test were performed to evaluate the differences between the periods.Results:The mean PAR score of 34.75 at T1 was reduced to 3.35 and 3.05 at T2 and T3, respectively, succeeding in a 90.35% reduction with treatment. At T1-T2 and T1-T3, maxillary intercanine and intermolar width and mandibular intercanine width increased significantly. Although intercanine and intermolar widths decreased in both arches at T2-T3, only maxillary intercanine width showed a small, but statistically significant decrease (0.09 mm, p=0.001). Value of SNB angle, Md1-NB (mm), Md1-NB (degrees), and E plane-lower lip increased significantly at T1-T2 and T1-T3. Therefore, treatment resulted in mandibular incisor and lower lip proclination. All of the posteroanterior cephalometric changes were statistically significant except facial width changes at T1-T2.Conclusions:This study represented satisfactory results and a good follow-up stability with the Damon system. The Damon system can be used for nonextraction treatment in patients with moderate crowding.